PENGARUH PENGENDALIAN INTERNAL, MORALITAS INDIVIDU DAN KEPUASAN KERJA TERHADAP KECENDERUNGAN KECURANGAN AKUNTANSI (Studi Pada Karyawan PT NPI Kabupaten Boyolali) - Ameilia, Deva; Afandi, Pandi; Putra, Yanuar Surya; Puspita, Maria Entina (UNPERBA, 2025)
Accounting fraud was discovered in several companies due to pressure on financial targets. Its caused by internal control, individual morality and employee job satisfaction. The purpose this research to determine the influence of internal control, individual morality and job satisfaction on accounting fraud among PT NPI employees. From the results of the t test it is known that control has a significant effect, while individual morality and job satisfaction have no effect on the tendency for accounting fraud at PT NPI. The F test results of the three variables simultaneously influence the tendency for accounting fraud. As much as 61.3% is influenced by this variable, while the remaining 38.7% is influenced by other variables. Company must maintain and improve internal control and employee job satisfaction, and the employees always maintain good morality.